Characterization of infections related to health care in an intensive care unit in Acre (Research, Society and Development, 2022)
Hospitalized individuals are subject to the occurrence of Health Care-Related Infections (IRAS), responsible for the increase in public expenditures and impact on the length of stay. Objective: to analyze cases of Health Care-Related Infections in patients assisted in an Intensive Care Unit in Acre. Methods: epidemiological, retrospective study, carried out in an Urgent and Emergency Hospital in Acre, in 2019. Data were collected through the notification forms of the unit's hospital infection control commission, organized in tables and analyzed through the Descriptive statistics. Results: the highest occurrence occurred in males (66%). It was not possible to assess the average age of the individuals, as this information was absent in 32% of the notification forms, as well as in 26% of them, there was no information about the reason for hospitalization, but it was observed that the most frequent topography between the cases identified were hospitalizations due to accidents and violence (24%). Mechanical ventilation was performed in most patients (59%) and Pseudomonas aeruginosa was the main pathogen found (39%). The most frequent biological material for pathogen isolation was tracheal secretion (70%). Regarding the clinical outcome, in (61%) of the records this information was also absent, however, in view of what was possible to assess (31%) of the individuals died. Conclusion: Infections Related to Health Care are a current reality within intensive care units, affecting a significant number of individuals in Acre, and it is important to implement measures that can change this reality, as well as it is urgent to improve records in the notification forms so that more concrete assessments can be carried out.